PEMAHAMAN GURU TENTANG PENILAIAN DALAM KURIKULUM MERDEKA: KASUS DI KABUPATEN BANTUL(TEACHER'S UNDERSTANDING OF ASSESSMENT IN THE MERDEKA CURRICULUM: A CASE IN BANTUL REGENCY) - Sudrajat, Ahmad Kamal; Suyanto, Slamet; Limiansi, Kintan; Aprilisa, Ema; Suratsih, Suratsih; Subiantoro, Agung Wijaya; Nugroho, Ahmad Iskak (Universitas Negeri Yogyakarta, 2025)
Changes in social and technological aspects demand curriculum changes in education. Curriculum changes were made to create capable human beings according to the era. The Indonesian Ministry of Education has responded to these changes by implementing the